Analysis Design of Tour Guide Markeplace Information System in Bali - Krishna A P, Dewa Agung; Angga Prabawa, I Nyoman; Sri Ariyani, Ni Wayan (International Journal of Engineering and Emerging Technology, 2019)
Bali as a world tourist destination where most Balinese people work in tourism. One of the professions that are mostly occupied by Balinese people in the field of tourism is as a freelance Tour Guide. Most freelance Tour Guides in Bali still use the old ways of marketing such as world of mouth or only use recommendations from person to person. Many freelance Tour Guides in Bali complain that the rise of digital transportation is felt to diminish their marketing area. But now some of the freelance Tour Guides have begun to use their social media as a marketing tool using information technology. The solution that can be developed in order to improve the competitiveness of Bali's local freelance Tour Guide in order to compete in the current digital era is to create a marketplace. With this marketplace, this freelance Tour Guide has a place to promote their products. Besides that, for tourists who want to travel to Bali, it will be easier to find and choose Tour Guides as desired and the criteria of tourists.